The Invasive Plant Maeopsis eminii: A Key Dietary Resource for Primates in the Tropical Rainforests of West Java, Indonesia - Noer, Mohamad Isnin; Lestari, Alvita Dwi; Ramadhini, Kiky; Prasetya, Priya Yuga; Sedayu, Agung; Komala, Ratna (HAYATI Journal of Biosciences, 2025)
Animal-plant interactions are crucial for understanding the ecological dynamics and predicting ecosystem changes. This study explores the role of the invasive plant Maesopsis eminii in the Bodogol Nature Reserve, Gunung Gede National Park, West Java, Indonesia, focusing on its interaction with diurnal vertebrate species. Primates, including Javan gibbon and Javan langur, were identified as primary consumers of Maesopsis eminii, with Javan gibbon showing the highest consumption rates. Dietary analysis revealed that both primate species utilized M. eminii fruits and leaves, whereas Javan gibbons relied more on Maesopsis eminii than Javan langurs. Other vertebrates, such as squirrels and birds, are occasional visitors with minimal fruit consumption. This study highlights that Maesopsis eminii is a primary resource of Javan gibbon, Javan langur, and Javan surili. This nearly year-round fruiting plant is crucial for supporting primate populations, especially given its contribution to their diet. Considering the mutualistic interaction between Maesopsis eminii and its visitors, the Javan gibbon was the only species that probably dispersed seeds through endozoochory, making this primate species a crucial part of the dispersal of Maesopsis eminii in Gunung Gede National Park. Because invasive plants can threaten native flora and fauna, future studies must emphasize balancing the beneficial and detrimental effects.